PATHOLOGICAL PHYSIOLOGY OF POSTHEMORRHAGIC ANEMIA - Rakhimova Gulnoz Shamsiyevna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation.  Blood  loss  is  a  compleх  of  pathological  disorders  and compensatory reactions directed against a decrease in the volume of circulating blood and  hypoxia  caused  by  a  decrease  in  the  respiratory  function  of  the  blood. Posthemorrhagic shock is a shock that occurs as a result of abundant acute blood loss. A decrease in the volume of circulating blood, a drop in blood pressure, a violation of microcirculation, disorders of the blood supply to vital organs (brain, heart, kidneys), the  development  of  hypoxia,  acidosis  and  intoxication,  "vicious  circles"  in  the pathogenesis leads to death. Post-hemorrhagic anemia-develops as a result of blood loss.